Chongqing 2035 : An Innovation Strategy to Climb Up the Value Chain and Create the Conditions for a Skilled Labor Force - World Bank (World Bank, Washington, DC, 2019)
The innovation economy has become a driving force in transforming entire industries, which has been happening at an accelerated pace. Cities are making massive investments in innovation and research and development (R&D) to support and attract technology-driven industries that are leading the digital revolution and disrupting established markets. To succeed in this transformation, a strong and skilled labor force is the most crucial factor. Human capital, meaning the skills, knowledge, and experience of the labor force, is critical for future economic development and innovation.Traditionally, Chongqing has been a city of production, focusing on the application of technology rather than its development and innovation. However, while this has served the city well in the past, Chongqing’s low innovative capacity puts it at risk of missing out on future economic opportunities. This problem is exacerbated by a shortage of highly skilled labor and by a mismatch between available jobs and the existing workforce.